A new species of Draconarius Ovtchinnikov, 1999 (Araneae, Agelenidae) from northeastern Pakistan - Zamani Alireza (Pensoft Publishers, 2022)
A new species of agelenid spiders, Draconarius nathiagalicus sp. nov., is described and illustrated on the basis of two male specimens collected in Nathia Gali, northeastern Pakistan. This is the fourth species of the genus reported from this country, all belonging to the venustus species-group.